Empowering UMKM Members Of KSPPS Nusantara Through Optimizing Sharia Financing For Sustainable Economic Growth - syuhada' syuhada'; Elis Zunita Anzar Wati; Anggilah Mawarni; Umu Farikhatus Sa'bandiyah (Shof Literacy Community, 2024)
The program